(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The Lancaster in-house code is a time-domain analysis code, developed especially for the TALOS wave energy converter, a novel wave energy conversion technology. The TALOS wave energy converter is a point absorber-like wave energy converter, but with a unique power take-off (PTO) system. The whole PTO system is fully enclosed within the structure, hence no moving parts are exposed to the harsh marine environments. The PTO of the TALOS WEC consists of a mass ball within the structure, with a number of springs and dampers (for instance, direct drives or hydraulic systems) connecting between the mass ball and the structure. Such an arrangement of the PTOs would make the PTO essentially non-linear, regardless whether the actual PTO dampers are linear or nonlinear as well as the linear springs. Therefore, a time domain analysis must be established for the TALOS WEC. Towards the goal, an in-house time-domain model has been developed at Lancaster University, and now it is to be validated via the delicated numerical models built using well-established commercial software (and in the future via experimental data). Within this framework, the present paper presents an effort for validation using the DNV SESAM commercial hydrodynamic and structural analysis software. To build a numerical model for TALOS WEC, the Lancaster in-house time domain code is based on the hybrid frequency-time domain approach. That is, the basic hydrodynamic parameters are analysed using the panel methods (WAMIT, HAMS, NEMOH), and then the relevant parameters are transformed for the Cummins’ time-domain equation, such as the added mass at infinite frequency, and the memory effect (the convolution terms). This work is an extension of the comparison between the in-house code and the DNV SESAM software, and the comparisons would include the relevant hydrodynamic analyses, the time-domain analyses with and without the TALOS PTO system, with the aims towards developing the validated tools of both the in-house code and the commercial software.